Konsepsi Wisata Halal di Aceh: Kajian Terhadap Wisata Budaya dan Sejarah di Provinsi Aceh - Dede Adistira (Jurnal Community, 2022)
This article aims to explain the concept of halal tourism in Aceh by using the concept of Developing of Halal Tourism. This study uses a literature study approach (library research) with data collection techniques sourced from relevant documents, books, articles, magazines, news, journals. The results of this study indicate that there are three criteria regarding the conception of halal tourism, namely (1) history, in tourism in Aceh in the form of records of historical places that can be seen when visiting the place. (2) culture, in halal tourism in Aceh, raises the roots culture in Aceh, for example the Seudati dance at the airport as a welcome to visiting tourists, (3) Islamic, which consists of facilities and infrastructure, culinary and service provision. The facilities and infrastructure in question are in the form of a Sharia hotel, a friendly place for every visitor. And finally, there is a strong collaboration between the government, the community and related stakeholders in carrying out the conception of halal tourism in Aceh.